Influência da participação orçamentária no desempenho gerencial - Werner, Camila da Silva Gonçalves (2023)
This research investigates the ways in which budget participation influences the managerial performance of controllers of industrial companies operating in Brazil. The research is based on the premise that human behavior results from the reciprocal influence of cognitive and personal, behavioral and environmental factors. This is descriptive research, with a quantitative approach, consisting of a survey carried out with the application of a questionnaire, with the support of the LinkedIn® business network. The sample is composed of 267 professionals who work as controllers, who have budgetary responsibility in the organization in which they work. For data analysis, descriptive statistical analysis procedures, factorial analysis and structural equation modeling were adopted. The results found showed a direct and positive influence of budgetary participation on psychological capital, autonomy at work, as well as commitment to budgetary targets, but not significant on managerial performance, which suggests that the effects of budget participation on performance may not occur directly, but based on other mediating variables. It was also observed that autonomy at work does not have a positive, direct and significant influence on managerial performance. The indirect paths between budgetary participation and managerial performance were confirmed through the additional analysis, through the mediation of the variables psychological capital, and commitment to budgetary targets. From these results, it is inferred that the promotion of budgetary participation influences the positive individual psychological capacities that make up the psychological capital, and that, thus, promote managerial performance. It is also inferred that the participation in the budget of the controllers in this sample promotes commitment to budgetary targets, which positively influences the performance of these professionals. Likewise, it appears in this sample that budgetary participation also has a positive influence on autonomy at work. However, autonomy at work did not significantly influence managerial performance. It is concluded that the participatory budgeting context influences individuals' cognitive, personal, behavioral and environmental factors, and that it indirectly benefits managerial performance. The autonomy at work, when not balanced, may present stressors to individuals, which may not enhance individual performance. The findings of this study contribute to the development of appropriate budget management practices that influence the cognition, behavior, and performance of managers in their work activities, in addition to contributing with the controllers in the knowledge of assumptions about their managerial performance in the budgeting context.